Creativity of Zhambyl Zhabayev in the context of integration processes - Aіnur KaztuganovaAklima Omarova,; Sultan, Yertay; Gulnar Ryskaliyeva, Bakyt Turmagambetova, (Opción, 2020)
The article is devoted to the personality, the heritage of the great Kazakh akyn Zhambyl Zhabayev (1946-1945) and specifics of revealing his image, poetic texts in the works of contemporary composers. Its goal -is to identify the innovative features of "Homer of the 20th century" in terms of the development of national traditional music and the context of the practice of the embodiment of this significant figure for Soviet culture in music and theatre. In this regard, first of all, the methods of comparative analysis are used.